Marketing and Finance Management Training for Micro Small and Medium Enterprises Instructions for Sleman Creative House - Anis Okta Cahyaningrum; Agung Utama; Tony Wijaya; W Winarno; Rullyana P. Mamengko (Salus Publica: Journal of Community Service, 2023)
The purpose of this community service is to give members of Micro, Small and Medium Businesses (MSMEs) under the Sleman Creative House an introduction to management. The Sleman Regency Industry and Trade Office established the Sleman Creative House as a platform to help Micro, Small, and Medium-Sized Businesses (MSMEs) in the Sleman region. PPM tasks are completed online through Zoom. 44 participants make up the targeted audiences, who are Micro, Small and Medium-Sized Businesses (MSMEs) under the Sleman Creative House. The activity was conducted by first delivering the content, then having a group discussion about the challenges the training participants encountered running their businesses. Financial management, social media-based digital marketing management, and turnover mastery are covered in the management introduction. The pre-test, process evaluation, and post-training using the post-test provide evidence of the success of the implementation of MSME training. PPM activities went off without a hitch. The program was enthusiastically followed by the participants throughout. The introduction of marketing and financial management is anticipated to be able to enhance the skills of Micro, Small and Medium Businesses (MSMEs) under the Sleman Creative House, which have a variety of companies including catering, batik, souvenirs, tourist transportation, and homestays.